Wnt and Hedgehog Gene Pathway Expression in Serous Ovarian Cancer. Issue 6 (1st August 2011) - Schmid, Seraina; Bieber, Marcia; Zhang, Fang; Zhang, Mallory; He, Biao; Jablons, David; Teng, Nelson N.H.
Abstract : Objective: Ovarian cancer has very heterogeneous histological classification, and response to therapy of the same grade and type varies. We studied genes in the Wnt and hedgehog (Hh) pathways, which are essential for embryonic development and which play critical roles in proliferation in a variety of human cancers. Variations in these pathway genes causing proliferation could play a role in the variation in tumor progression and response to therapy. Methods/Materials: Using real-time polymerase chain reaction, we studied 16 primary grade 3 International Federation of Gynecology and Obstetrics stage III serous ovarian cancer samples for expression of the Wnt pathway gene AXIN2, fibroblast growth factor 9, and Hh pathway gene expressions of glioma-associated oncogene 1, glioma-associated oncogene 2, patched homolog 1, patched homolog 2, Indian Hedgehog (HH), sonic HH, and Smoothened, a G protein-coupled receptor protein. Normal ovary epithelial cell line was used as control. Results: We found wide variation of up-regulation of pathway component and target genes in the primary tumor samples and apparent cross talk between the pathways. AXIN2, a Wnt target gene, showed increased expression in all serous ovarian cancer samples. Fibroblast growth factor 9 was also overexpressed in all tumors with greater than1000-fold increase in gene expression in 4 tumors. Expression of Hh pathway genes varied greatly. More than half of the tumor samples showed involvement of Hh signaling or pathway activation either by expression of transcription factors and Hh ligands or by overexpression of Indian HH/sonic HH and the receptor-encoding patched homolog 1/patched homolog 2. Conclusion: We found a wide variation in fold expression of genes involved in the Wnt and Hh pathway between patient samples.